“If You Know You Exist, It’s Just Marketing Poison”: Meanings of Tobacco Industry Targeting in the Lesbian, Gay, Bisexual, and Transgender Community - Smith, Elizabeth A. (American Public Health Association, 2008)
In the public health literature, it is generally assumed that the perception of “targeting” as positive or negative by the targeted audience depends on the product or message being promoted. Smoking prevalence rates are high among lesbian, gay, bisexual, and transgender (LGBT) individuals, but little is known about how they perceive tobacco industry targeting. We conducted focus groups with LGBT individuals in 4 US cities to explore their perceptions. Our findings indicated that focus group participants often responded positively to tobacco company targeting. Targeting connoted community visibility, legitimacy, and economic viability. Participants did not view tobacco as a gay health issue. Targeting is a key aspect of corporate–community interaction. A better understanding of targeting may aid public health efforts to counter corporate disease promotion.